It's alive in the laboratory of the mind: Frankenstein, thought experiment and facing the future of science. Issue 1 (1st March 2018) - Gil, Steven
Science fiction splices actuality, eventuality and imagination into creations that provide novel and sometimes highly influential perspectives on science and society. One of the greatest examples of this is Mary Shelley's Frankenstein – the infamous tale of a man who literally splices dead flesh into a new form and bestows this creation with life. By examining Frankenstein as a thought experiment, this article demonstrates how science fiction can become a commentary on scientific activity, give insight about where science might lead, and provide a resource for discussing and framing new science.